Influence of Developing Professional Communication on the Success of Postgraduate Research Supervisory - Balsam, A. Mustafa (WSEAS Press, 2015)
This paper focuses on the evaluation of graduate supervision and highlights the problem areas presently documented as significant areas of concern for both graduate students and their supervisors. It aims to understand supervision as pedagogy where effective communication between the student and supervisor would encourage the successful completion of the research project. Current literature on the supervisory feedback emphasis what types of feedback is given rather than how it is given and perceived and how students feel about and react to feedback. This research tries to attend to psychological theories to understand how much a feedback from a supervisor may effect the graduate student attitude and motivation to achieve his study goals.